Survival of Phytophthora cinnamomi and P. multivora in Lime-amended Bioclay® (LaBC®) and LaBC® plus organic material - Davison, Elaine; Tay, Francis (Water Corporation, 2011)
Lime–amended BioClay® (LaBC®) is a high pH product developed as a soil amendment for use on Bassendean Sands of the Swan Coastal Plain. Composted mulch is used to clean equipment used in its production and lower the pH of the final product. If this composted mulch is contaminated with Phytophthora cinnamomi (the dieback fungus) this soil borne pathogen might be inadvertently spread to uninfested properties. In order to determine the likelihood of this occurring, pine plugs colonised by either P. cinnamomi or the similar pathogen P. multivora, were incubated in LaBC® or LaBC® + organic material for up to 21 days. P. cinnamomi survived for less no more than 6 days in both products, while P. multivora survived for no more than than 6 days in LaBC®, and for no more than than 14 days in LaBC® + organic material. This experiment shows that there is minimal risk of LaBC® or LaBC® + organic material being a source of these pathogens.